Implementation of a deep learning model for segmentation of multiple myeloma in CT data - Gálík, Pavel; Nohel, Michal (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2024)
This paper deals with the implementation of a deep learning model for spinal tumor segmentation of multiple myeloma patients in CT data. Deep learning is becoming an important part of developing computer-aided detection and diagnosis systems. In this study, a database of 25 patients who were imaged on spectral CT and for whom different parametric images (conventional CT, virtual monoenergetic images, calcium suppression images) were reconstructed, was used. Three convolutional neural network models based on the nnU-Net framework for lytic lesion segmentation were trained on the selected data. The results were evaluated on a test database and the trained models were compared.
Keywords: multiple myeloma; computed tomography; deep learning; nnU-Net; segmentation; monoenergetic image; calcium suppress image